2014
DOI: 10.1080/11263504.2013.870247
|View full text |Cite
|
Sign up to set email alerts
|

Using minirhizotrons to estimate fine root turnover rate as a forest ecosystem health indicator in Moso bamboo forests in Dagang mountain

Abstract: The contribution of fine roots to forest ecosystem health (FEH) is still poorly understood, although fine roots are recognized to provide benefits to ecosystems. To address the relationship between fine roots and forest health, minirhizotrons was used to observe fine root (, 2 mm) dynamics during a 1-year period in nine Moso bamboo [Phyllostachys pubescens Mazel ex J. Houz.] plots having three levels of forest health (health, general health, and sub-health) 6 months after minirhizotron installation in the Daga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 61 publications
0
0
0
Order By: Relevance
“…A previous study by Xue et al. (2015) found a turnover of the fine roots of P. pubescens in China that ranged between 0.68 ± 0.19 and 1.37 ± 0.32 year −1 , depending on the forest health condition. To the best of our knowledge, the turnover rate of soil C for P. nigra , P. aurea and P. aureosulcata has not been studied yet.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…A previous study by Xue et al. (2015) found a turnover of the fine roots of P. pubescens in China that ranged between 0.68 ± 0.19 and 1.37 ± 0.32 year −1 , depending on the forest health condition. To the best of our knowledge, the turnover rate of soil C for P. nigra , P. aurea and P. aureosulcata has not been studied yet.…”
Section: Discussionmentioning
confidence: 92%
“…Gill and Jackson (2000) reviewed multiple root turnover rates for terrestrial ecosystems and reported a value of about 0.52 year −1 for temperate grassland. A previous study by Xue et al (2015) found a turnover of the fine roots of P. pubescens in China that ranged between 0.68 ± 0.19 and 1.37 ± 0.32 year −1 , depending on the forest health condition. To the best of our knowledge, the turnover rate of soil C for P. nigra, P. aurea and P. aureosulcata has not been studied yet.…”
Section: Bamboo Soc and Potential Carbon Inputsmentioning
confidence: 90%